Pengaruh Tingkat Pendidikan dan Prestasi Kerja terhadap Promosi Jabatan pada Sekolah Tinggi Ilmu Ekonomi Serelo Lahat - Titi Hasanah; Markus Markus; Saparudin Saparudin (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research aims to see the influence of education level and work performance on job promotion at the Serelo Lahat College of Economics. This research uses a descriptive study with a quantitative approach. The population of this research is all 160 employees of STIE Serelo Lahat. The random sampling method used took 25% of the respondents, so the total sample was 40 people. The research results found that there was a significant influence of work performance (X1) on job promotion (Y) with analysis of the t-calculated value of work performance (X1) of 6.699> t-table value at the actual level of 0.05 with degrees of freedom n-2 = 38 obtained t-table = 2.024 or with a significant level of 0.000 (P-value < 0.05 and there is also an essential influence between the level of education (X2) on promotion (Y) and the analysis of the t-calculated value of the level of education (X2) of 3.762> t-table value at a fundamental level of 0.05 with degrees of freedom n-2 = 38 obtained t-table = 2.024 or with a sizeable significant level of 0.001 (P-value < 0.05). There is a significant correlation between work performance and The level of education that influences job promotion. In conclusion, there is a significant influence between work performance and education level on job promotion. Keywords: level of education, work performance, promotion